Using seam to better understand born globals. A spanish case - Rastrollo-Horrillo, María Ángeles; Martín-Armario, Julia (My University, 2017)
This work presents a systematic overview of the opportunities and challenges for international ventures. Moreover, it seeks to reflect on success-factors of launching a venture in international context and how Socio-Economic Approach to Management (SEAM) can help. Using a practical case study, we discuss the limitations of the “state of art” in BGs and reflect on what SEAM can provide in understanding the main managerial complexities faced by BGs and in leading BGs change in order that they develop the dynamic capabilities to succeed in International markets.
Keywords: Multinacionales; SEAM; Born-Globals; Dynamic Capabilities